A Root-MUSIC-Like Direction Finding Method for Cyclostationary Signals - Yide Wang; Pascal Chargé (EURASIP Journal on Advances in Signal Processing, 2005)
We propose a new root-MUSIC-like direction finding algorithm that exploits cyclostationarity in order to improve the direction-of-arrival estimation. The proposed cyclic method is signal selective, it allows to increase the resolution power and the noise robustness significantly, and it is also able to handle more sources than the number of sensors. Computer simulations are used to show the performance of the algorithm.